Environmental chemistry - Manahan, Stanley E., 1937- (CRC Press, Taylor and Francis Group, 2022)
"With clear explanations, real-world examples and updated ancillary material, the 11th edition of Environmental Chemistry emphasizes the concepts essential to the practice of environmental science, technology and chemistry. The format and organization popular in preceding editions is used, including an approach based upon the five environmental spheres and the relationship of environmental chemistry to the key concepts of sustainability, industrial ecology and green chemistry. The new edition provides a comprehensive view of key environmental issues, and significantly looks at diseases and pandemics as an environmental problem influenced by other environmental concerns like climate change"- Resumé vydavatel
Keywords: environmentální chemie; environmental chemistry; monografie; monographs